Effectiveness of Strongyloides Recombinant IgG Immunoreactive Antigen in Detecting IgG and IgG4 Subclass Antibodies for Diagnosis of Human Strongyloidiasis Using Rapid Immunochromatographic Tests - Boonroumkaew, Patcharaporn (Diagnostics (Basel), 2020)
Human strongyloidiasis is an important soil-transmitted helminthiasis that affects millions worldwide and can develop into fatal systemic strongyloidiasis in immunosuppressed patients. We have developed two new rapid and simple-to-use immunochromatographic test (ICT) kits for rapid serodiagnosis that support stool examination for clinical diagnosis. Strongyloides stercoralis recombinant IgG immunoreactive antigen (GenBank: AAB97359.1; rSsIR-based ICT kit) was used for detection of IgG and IgG4 antibodies. The diagnostic efficacy of both kits was evaluated using human serum samples from strongyloidiasis patients, healthy individuals, and those with other parasitosis. At a prevalence of infection of 36.4%, the diagnostic sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of the rSsIR-based IgG ICT kit were 91.7%, 83.8%, 76.4%, 94.6%, and 86.7%, respectively, and those of the rSsIR-based IgG4 ICT kit were 78.3%, 84.8%, 74.6%, 87.3%, and 82.4% respectively. The concordance between the two kits was 89.7%. The recombinant antigen can be produced to an unlimited extent and the kits can be used as point-of-care diagnostic tools and in large-scale surveys in endemic areas throughout tropical regions without necessitating additional facilities or ancillary supplies.